2003
DOI: 10.7861/clinmedicine.3-3-235
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicine: evidence base, competence to practice and regulation

Abstract: -This paper describes the current status and evidence base for acupuncture, homeopathy, herbal and manipulative medicine, as well as the regulatory framework within which these therapies are provided. It also explores the present role of the Royal College of Physicians' Subcommittee on Complementary and Alternative Medicine (CAM) in relation to these developments. A number of CAM professions have encouraged the Royal College of Physicians Subcommittee to act as a reference point for their discussions with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Previous reports had shown that some of the herbal medicine could interact with standard cancer treatments and/or confer adverse effects [6,12,18]. Such effects may be caused by the presence of contaminants in the herbs such as heavy metals or by misidenti- [11]. One of the well-known herbs that could cause herb-drug interaction is St. John's wort.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports had shown that some of the herbal medicine could interact with standard cancer treatments and/or confer adverse effects [6,12,18]. Such effects may be caused by the presence of contaminants in the herbs such as heavy metals or by misidenti- [11]. One of the well-known herbs that could cause herb-drug interaction is St. John's wort.…”
Section: Discussionmentioning
confidence: 98%
“…However, scientific research on CAM therapies can be difficult due to unique barriers. These include a lack of interest among medical researchers, limited availability of research funds, and difficulties applying conventional research methods to studying alternative therapies [18]. For example, medical researchers often have little scientific interest in acupuncture because its theory depends on non-scientific concepts such as "vital energy".…”
Section: Effectivenessmentioning
confidence: 99%
“…Commercial research funds are limited because CAM therapies cannot be patented and do not generate large profits to drive research and marketing. Government research funds are limited because the scientific community remains skeptical of CAM theory and the validity of its methods [18].…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…CAM therapies propose a new relationship between patients and physicians, a holistic approach [4] to the patient and a re-evaluation of the psychosomatic component that include:…”
mentioning
confidence: 99%